Salmonella meningitis with thrombotic microangiopathy in an exclusively breast-fed infant: Case report - Swathy Subhash; Saravana Pandian; Suchitra Ranjit (Wolters Kluwer Medknow Publications, 2019)
Salmonella species is now a leading cause of meningitis in the developing world. We report a 6-month-old fully vaccinated baby girl who presented with high-grade fever and seizures. Her CSF and blood cultures grew non-typable Salmonella strains. The child was treated with antibiotics and anti-epileptics and discharged home after 2 weeks of hospital stay.Children with salmonella meningitis may present with life-threatening manifestations in the absence of gastrointestinal symptoms.